Approximation of Magnetic Curve of Trolleybus Traction Motors - V. V. Ravino; V. N. Satsukevitch; P. M. Haliamau (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An analysis of the known methods for magnetic curve approximation of electrical machines has been carried out and their disadvantages have been revealed. It is established that six degree algebraic polynomial provides the best approximation of traction motor magnetic curve. Its coefficients have been determined and they make it possible to approximate magnetic curve of trolleybus traction DK-210A3-type motor with an accuracy which is sufficient for practical calculation.